Targeted gene panel analysis of Japanese patients with maturity‐onset diabetes of the young‐like diabetes mellitus: Roles of inactivating variants in the ABCC8 and insulin resistance genes. Issue 3 (12th December 2022) - Yorifuji, Tohru; Watanabe, Yoh; Kitayama, Kana; Yamada, Yuki; Higuchi, Shinji; Mori, Jun; Kato, Masaru; Takahashi, Toru; Okuda, Tokuko; Aoyama, Takane
Abstract: Aims/Introduction: To investigate the genetic background of Japanese patients with suspected maturity‐onset diabetes of the young (MODY). Materials and Methods: On 340 proband patients referred from across Japan, genomic variants were analyzed using a targeted multigene panel analysis combined with the multiplex ligation probe amplification (MLPA) analysis, mitochondrial m.3243A > G analysis and methylation‐specific polymerase chain reaction of the imprinted 6q24 locus. Pathogenic/likely pathogenic variants were listed according to the 2015 American College of Medical Genetics and Genomics and the Association for Molecular Pathology criteria. Additionally, variants with a population frequency <0.001 and Combined Annotation Dependent Depletion score >20 (CS >20) were listed as rare variants of uncertain significance‐CS >20. Results: A total of 157 pathogenic/likely pathogenic variants and 44 rare variants of uncertain significance‐CS >20 were identified. In the pathogenic/likely pathogenic variants, alterations in the GCK gene were the most common (82, 52.2%) followed by HNF1A (29, 18.5%), HNF4A (13, 8.3%) and HNF1B (13, 8.3%). One patient was a 29.5% mosaic with a truncating INSR variant. In the rare variants of uncertain significance‐CS >20, 20 (45.5%) were in the genes coding for the adenosine triphosphate‐sensitive potassium channel, KCNJ11 or ABCC8, and four were in the genes of the insulin‐signaling pathway, INSR and PIK3R1 . Four variants in ABCC8 were previously reported in patients with congenital hyperinsulinism, suggesting the inactivating nature of these variants, and at least two of our patients had a history of congenital hyperinsulinism evolving into diabetes. In two patients with INSR or PIK3R1 variants, insulin resistance was evident at diagnosis. Conclusions: Causative genomic variants could be identified in at least 46.2% of clinically suspected MODY patients. ABCC8 ‐MODY with inactivating variants could represent a distinct category of MODY. Genes of insulin resistance should be included in the sequencing panel for MODY. Abstract : The most comprehensive and one of the largest genomic variant analyses of MODY‐like diabetes in East Asians. Found the importance of inactivating variants in the ABCC8 and insulin resistance genes.